Facial Traumatic Injury in a Dog - Surgical Reconstruction with Rotational Transposition Flap - Alves Trindade, Wesley; Vicente, Johany Diego; da Cruz Silva , Jeferson; Barros Bezerra, Francisca; Quessada, Ana Maria; de Melo Germano, Ricardo (Acta Scientiae Veterinariae, 2023)
Background: Bite injuries are commonly found in small animal clinics, especially in male dogs, due to their habits of fighting and territorial disputes. In general, the lesions are treated with the use of compresses and bandages, however, it is extremely important to carefully evaluate the site, in order to carry out the appropriate treatment. In cases of tissue loss, an increasingly used practice is reconstructive surgery, which launches alternatives for treatment through flaps and skin grafts, promoting healing and satisfactory aesthetic repair. This report describes the case of a dog with a facial bite, treated with reconstructive surgery. Case: A 5-year-old male mixed-breed dog, with a body mass of 5 kg, was treated and submitted to a physical examination, due to the owner’s complaint that he had been attacked by another dog, causing a bite on the face. On physical examination, the animal showed normal vital parameters, except for mild hyperthermia due to rectal temperature (39.5°C). On the face, it was possible to observe a lacerative lesion in the temporomandibular and masseteric regions, with loss of skin and muscle, in addition to having an aspect of infection and necrosis. To describe the hematological profile, a blood count was performed, showing no changes. In the biochemical tests, the present alteration was a slight increase in Alkaline Phosphatase (393.8 IU/L). Surgical treatment was indicated through facial reconstruction with a skin graft. After performing the antisepsis, the lesion was debrided, the edges were regularized and the injured tissue was curetted. For reconstruction of the defect, we used a flap obtained through a perpendicular incision at the base of the ear, in a caudal direction, and this flap was pulled and transposed over the wound. Flap synthesis was performed with 3-0 nylon thread. After surgery, a compressive bandage was performed, which was removed after 24 h. It was indicated to avoid exertion in the area and to return in 10 days for the evaluation of the surgery and removal of the stitches. Discussion: Traumatic injuries in animals are being increasingly reported, with male and non-neutered dogs being the most prevalent patients. This report is in line with other studies, with the patient’s profile being a male dog, with an average age, in line with the literature. In general, in certain types of wounds, the affected animals can develop sepsis and even progress to death, however, in this case the patient did not show changes in vital parameters and in hematological tests. Reconstructive surgeries are performed with the aim of correcting skin defects and knowledge of the available techniques is important. It is also necessary to carry out a good planning, in order to avoid complications in the trans and postoperative period. In the present case, we chose to use a flap obtained through an incision perpendicular to the base of the ear, transposing it over the wound, in addition to relieving tissue tension through skin divulsion, increasing its elastic potential. The use of bandages is considered extremely important for the success of the surgical procedure, as it provides an efficient barrier against infections, trauma and adhesions. However, we emphasize the need to use ointments, gauzes and bandages concomitantly, in order to have the desired success in the postoperative period. In addition to proper surgical techniques, pain management and infection control are important for patient recovery. It is important to use non-steroidal anti-inflammatory drugs and opioids to obtain analgesia, in addition to antibiotic therapy before and after surgery. The reported case demonstrated that lesions in dogs with skin loss can be reconstructed using skin flaps, with an excellent recovery and good prognosis, as was the case with the patient in this report. Keywords: canine, reconstructive surgery, lacerative wound, bite. Descritores: canino, cirurgia reconstrutiva, ferida lacerativa, mordedura.